Basal cell carcinoma of the prostate: a case report responding to the FGFR inhibitor pemigatinib and literature review. Issue 4 (July 2022) - Rebhan, Katharina; Wasinger, Gabriel; Hassler, Melanie R.; Shariat, Shahrokh F.; Compérat, Eva M.
Abstract : Purpose of review: Due to the limited number of cases, there are no guidelines for basal cell carcinoma (BCC) of the prostate. This review combines an unpublished case report of a 55-year-old patient with BCC with an assessment of the latest literature. Recent findings: BCC of the prostate has previously been described in only approximately 140 cases. We describe the diagnostic process, including the uropathological and DNA-sequencing results, which allowed us to start an experimental treatment with pemigatinib. BCC of the prostate is associated with an aggressive biological and clinical behavior, such as recurrence and metastasis. Several immunohistochemical stainings are available to differentiate BCC from adenocarcinoma of the prostate. Based on pathology and results from next-generation sequencing (NGS), patients can be offered targeted therapies. Summary: With the aid of histological work-up and immunostaining, prostatic BCC can be accurately diagnosed. Our patient underwent radical prostatectomy and staged extended lymphadenectomy due to lymph node recurrence. The patient subsequently developed progressive disease and was treated with the FGFR-inhibitor pemigatinib. The patient's liver metastasis significantly responded. The present case confirms the possibility of aggressive behavior of prostatic BCC and highlights the importance of a thorough uropathological and molecular biological analysis with a precision medicine strategy.